2022
DOI: 10.1021/acsinfecdis.2c00172
|View full text |Cite
|
Sign up to set email alerts
|

Suite of TMPRSS2 Assays for Screening Drug Repurposing Candidates as Potential Treatments of COVID-19

Abstract: SARS-CoV-2 is the causative viral pathogen driving the COVID-19 pandemic that prompted an immediate global response to the development of vaccines and antiviral therapeutics. For antiviral therapeutics, drug repurposing allows for rapid movement of the existing clinical candidates and therapies into human clinical trials to be tested as COVID-19 therapies. One effective antiviral treatment strategy used early in symptom onset is to prevent viral entry. SARS-CoV-2 enters ACE2-expressing cells when the receptor-… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 42 publications
0
7
0
Order By: Relevance
“… 52 In another study, a team of investigators developed a fluorogenic high-throughput in vitro screening assay through which a total of 6030 drug repurposing candidates from National Center for Advancing Translational Sciences (NCATS) annotated libraries were evaluated for inhibiting SARS-CoV-2 replication in Calu-3 cells. 53 Next, a suite of subsequent assays, including a mass spectrometry-based detection assay and a cell-based SARS-CoV-2 pseudotyped particle entry assay, was developed to confirm and assess the hits from the biochemical screen, among which camostat, nafamostat, PCI-27483, otamixaban, and 2 peptidomimetic inhibitors of TMPRSS2 were identified.…”
Section: Repurposing Drugs For Treating Cardiovascular Manifestations...mentioning
confidence: 99%
See 2 more Smart Citations
“… 52 In another study, a team of investigators developed a fluorogenic high-throughput in vitro screening assay through which a total of 6030 drug repurposing candidates from National Center for Advancing Translational Sciences (NCATS) annotated libraries were evaluated for inhibiting SARS-CoV-2 replication in Calu-3 cells. 53 Next, a suite of subsequent assays, including a mass spectrometry-based detection assay and a cell-based SARS-CoV-2 pseudotyped particle entry assay, was developed to confirm and assess the hits from the biochemical screen, among which camostat, nafamostat, PCI-27483, otamixaban, and 2 peptidomimetic inhibitors of TMPRSS2 were identified.…”
Section: Repurposing Drugs For Treating Cardiovascular Manifestations...mentioning
confidence: 99%
“…inhibitor to treat leukemia and other malignancies Han et al49 and Aman et al91 CyclosporineA calcineurin inhibitor used to prevent organ rejection after transplantation and in certain autoimmune diseases Dittmar et al50 and Sauerhering et al92 Otamixaban A direct factor Xa inhibitor that was investigated for the treatment for acute coronary syndrome Shrimp et al52 and Hempel et al95 SulfasalazineAn anti-inflammatory to treat ulcerative colitis and rheumatoid arthritis Han et al56 DexamethasoneA corticosteroid used to treat inflammation Fava et al57 and The RECOVERY Collaborative Group96 Baricitinib A Janus kinase inhibitor used for the treatment of rheumatoid arthritis and alopecia areata Fava et al57 and Selvaraj et al97 Tacrolimus A calcineurin inhibitor used to prevent organ rejection after transplantation and in certain autoimmune diseases Fava et al57 Zotatifin A selective inhibitor of the eukaryotic translation initiation factor 4A with potential antineoplastic activity Gordon et al25 and Fava et al57 Nintedanib A tyrosine kinase inhibitor used for the treatment of idiopathic pulmonary fibrosis…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In clinical trials, it has shown to be safe but not as efficient as the control used. It has reappeared again as a drug of interest because of its ability as a TMPRSS2 inhibitor and hence a potential COVID-19 therapy [ 61 ].…”
Section: Proteases As Targetsmentioning
confidence: 99%
“…Hoffmann et al first demonstrated that the SARS-CoV-2 S protein is primed via the TMPRSS2 protease, indicating that TMPRSS2 inhibitors may block viral invasion [ 9 , 12 ], SARS-CoV-2 entry, and coronavirus disease 2019 (COVID-19) outcomes [ 13 ]. These findings suggest that the inhibition of TMPRSS2 expression may protect against cancer progress as well as SARS-CoV-2 invasion.…”
Section: Introductionmentioning
confidence: 99%